Phytochemistry and pharmacological activities of Annona genus: A review - Siti Kusmardiyani; Yohanes Andika Suharli; Muhamad Insanu; Irda Fidrianny (Current Research on Bioscences and Biotechnology, 2020)
Plants have been significantly used in traditional medicine by a variety of societies since antiquity, and knowledge of their safety, efficacy, and quality value can be developed through further research. The Genus Annona consisting of 119 species has been extensively researched and proven to have a diverse range of pharmacological activities such as antioxidant, antiulcer, antidiarrheal, and antiparasitic. This is because the Annona plants possess a great number of phytochemicals found in almost every part of the plant, which can be isolated to be developed into herbal medicine. Phytochemicals are classified into several classes, such as Annonaceous acetogenin, alkaloids, flavonoids, and essential oils. This article was created by collecting 137 research articles which discuss phytochemical compounds from 38 species and the pharmacological activity from 13 species.